Navigating Aging with Comorbidities: A Study on Quality of Life Among the Elderly in Urban Puducherry - bon. S, Sivasankari; Rajalakshmi S, Rajalakshmi S (Journal of Neonatal Surgery, 2025)
Background: The aging population faces increasing challenges due to comorbid illnesses that significantly impact their quality of life (QoL). Understanding the factors influencing QoL in elderly individuals is crucial for developing targeted healthcare interventions.Aim: This study aims to assess the QoL among elderly individuals with comorbid conditions residing in selected urban areas of Puducherry. Methodology: A descriptive cross-sectional study was conducted among 100 elderly individuals aged 60 years and above with at least one diagnosed comorbid condition. Participants were selected using a convenience sampling technique. Data were collected using the WHOQOL-BREF questionnaire, which evaluates QoL across four domains: physical health, psychological well-being, social relationships, and environmental factors. Descriptive statistical methods were applied for analysis. Results: The findings revealed that the mean overall QoL score was 59.9 (SD = 11.8), with the highest mean score observed in social relationships (64.8 ± 11.7) and the lowest in environmental factors (55.6 ± 13.2). Statistical analysis indicated that age, marital status, education level, and comorbid illnesses were significantly associated with QoL (p < 0.05). Among the comorbid conditions, cardiovascular disease had the most substantial negative impact on QoL. Conclusion: The study emphasizes the need for holistic healthcare strategies that address both medical and psychosocial aspects of aging. Strengthening social support, enhancing healthcare accessibility, and implementing community-based interventions can significantly improve QoL in elderly individuals with comorbid illnesses.